2016
DOI: 10.1186/s40064-016-2889-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of models for estimating methane emission factor for enteric fermentation of growing-finishing Hanwoo steers

Abstract: The methodology provided by the Intergovernmental Panel on Climate Change (IPCC) guidelines is widely used for estimating enteric methane (CH 4 ) production by cattle. No attempt other than the default values in the IPCC Tier 1 has been made for estimating CH 4 emission from Hanwoo, a dominant beef species in Korea raised in a unique feeding system. The objective of this study was to compare models for estimating the CH 4 emission factor (MEF; kg CH 4 /head/year) for enteric fermentation in Hanwoo steers. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…In this study, the MEF was 57.59 in the SF group and 61.18 in the TMR, comparable to the Korean inherent emission factor. Jo et al [ 56 ] analyzed several MEF prediction methods; Hanwoo steers MEF at the finishing stage was predicted as 33.9 when the IPCC Tier 2 method was used. However, Bharanidharan et al [ 7 ] reported that Hanwoo steers MEF measured through respiration chambers was 35.1 in SF and 49.4 in TMR, higher than those predicted by Jo et al [ 56 ] and lower than the measured values in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the MEF was 57.59 in the SF group and 61.18 in the TMR, comparable to the Korean inherent emission factor. Jo et al [ 56 ] analyzed several MEF prediction methods; Hanwoo steers MEF at the finishing stage was predicted as 33.9 when the IPCC Tier 2 method was used. However, Bharanidharan et al [ 7 ] reported that Hanwoo steers MEF measured through respiration chambers was 35.1 in SF and 49.4 in TMR, higher than those predicted by Jo et al [ 56 ] and lower than the measured values in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, annual emissions of CH 4 and N 2 O emission from the Hanwoo cattle manure management systems were almost 5.4 and 2.1 times, respectively higher than the values provided by IPCC. Jo et al reported that such variation might be attributed to the differences in feeding systems and cattle breeds as the values mentioned by IPCC values were estimated based on the studies conducted mainly in western countries [21]. Country-specific emission factors are, therefore, needed rather than using the values of the 2006 IPCC GL to develop effective and efficient GHG emission reduction strategies for the livestock industries.…”
Section: Comparison Of Greenhouse Gas Emissions With Intergovernmenta...mentioning
confidence: 99%
“…According to the Hanwoo traceability system, the number of cattle amounted to 3.07 million in 2019, representing more than 86% of the total cattle population in Korea [20]. Hanwoo cattle has been identified as the major contributor of the GHG emissions from the cattle production sector in Korea as well as showed higher enteric GHG emissions than other breeds [21,22]. However, none of the studies have estimated GHG emissions from Hanwoo cattle manure management systems, which acts as the main hindrance to developing national GHG emissions statistics for livestock sector in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Jika dilihat dari persen penurunannya, maka hasil estimasi dengan Tier 2 lebih rendah sekitar 21,82% sampai 27,86% dibandingkan dengan jika diestimasi menggunakan Tier 1. Seperti yang dilaporkan oleh Jo et al (2016), bahwa penghitungan dengan menggunakan Tier 2 di Korea dengan menggunakan faktor emisi local, memberikan nilai emisi yang lebih rendah 8 -14% dibandingkan dengan jika digunakan penghitungan dengan metode Tier 1.…”
Section: Penurunan Emisi Gas Metana Setelah Perubahan Metode Penghituunclassified